2016
DOI: 10.1186/s13068-016-0666-z
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous production of biohythane from hydrothermal liquefied cornstalk biomass via two-stage high-rate anaerobic reactors

Abstract: BackgroundBiohythane production via two-stage fermentation is a promising direction for sustainable energy recovery from lignocellulosic biomass. However, the utilization of lignocellulosic biomass suffers from specific natural recalcitrance. Hydrothermal liquefaction (HTL) is an emerging technology for the liquefaction of biomass, but there are still several challenges for the coupling of HTL and two-stage fermentation. One particular challenge is the limited efficiency of fermentation reactors at a high soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…This process consists of a two-stage production of hydrogen followed by methane production, which is known as biohythane (Cheng and Liu 2012). Biohythane is a type of clean energy that has advantages such as the reduction of fermentation time and a better control of the process due to the separation of the hydrogen and methane production stages (Liu et al 2013;Monlau et al 2013b;Si et al 2016). These two stages present great differences between them in terms of environmental, nutritional, and physiological conditions (Kongjan et al 2011).…”
Section: Biohythanementioning
confidence: 99%
“…This process consists of a two-stage production of hydrogen followed by methane production, which is known as biohythane (Cheng and Liu 2012). Biohythane is a type of clean energy that has advantages such as the reduction of fermentation time and a better control of the process due to the separation of the hydrogen and methane production stages (Liu et al 2013;Monlau et al 2013b;Si et al 2016). These two stages present great differences between them in terms of environmental, nutritional, and physiological conditions (Kongjan et al 2011).…”
Section: Biohythanementioning
confidence: 99%
“…)revealed the distribution of organic matter in the aqueous phase. TOC/TC was close to 1, indicating little inorganic carbonwas in the aqueous phase.The organic matter in the aqueous phase could be treated and converted to gas fuels (hydrogen and methane)[32]. Besides, the TN contentsof the aqueous phase were2.74-14.84g/L and the pH values were 7.09-8.64, indicatingthat there might bean abundance ofammonia in the aqueous phase.Ammonia was formed during HTL of…”
mentioning
confidence: 99%
“…Microbial community analysis revealed high amounts of bacteria capable of degrading N-heterocyclic and aromatic compounds such as Syntrophorhabdus and Synergistes (Usman et al, 2019). Si et al (2016) also reported numerous microorganisms associated with acidification and detoxification in long-term continuous AD experiments.…”
Section: Introductionmentioning
confidence: 95%